Lignocellulose-Based Bioproducts - Karimi, Keikhosro (Biofuel and Biorefinery Technologies, 2015)
This volume provides the technical information required for the production of biofuels and chemicals from lignocellulosic biomass. It starts with a brief overview of the importance, applications, and production processes of different lignocellulosic products. Further chapters review the perspectives of waste-based biofuels and biochemicals; the pretreatment of lignocellulosic biomass for biofuel production; cellulolytic enzyme systems for the hydrolysis of lignocelluloses; and basic and applied aspects of the production of bioethanol, biogas, biohydrogen, and biobutanol from lignocelluloses. This book is recommended for researchers and engineers and particularly students taking biofuel courses at graduate level.